(untitled) (Annual of the Faculty of Philosophy in Skopje, 2008)
Christianity has left deep roots in Macedonian history, and has had a great influence on the toponymy of Macedonia. A large number of Macedonian toponyms, in the Middle Ages and during the Ottoman rule, have a Christian origin, that is, they contain Christian elements. This is especially characteristic of settlements whose names are borrowed from Christianity. Among them, settlements with the names of the Creator-God/Theos, or derived from his name, deserve special attention. Such settlements are: Teovo, Bogomila, Pobozhje, Boži Grad, Bogacko, Bogovine, Bogdevo, Bogoselche, Božidol, Bogdanci and others. The Mother of God-Bogorodica was quite popular in Macedonia. Many settlements bore her name, or were derived from it. Settlements with the name of the Bogorodica are recorded in the area of ​​Delčevo, Kočani, Petrich, Melnik, Thessaloniki, Gevgelija, Hrupishta and others. A good portion of the recorded Christian settlements, under the same or slightly changed names, still exist today.